(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
This research focused on understanding recycling behavior and different factors affecting waste recycling of selected grade 12 Accountancy, Business, and Management (ABM) Strandstudents at Bestlink College of the Philippines. By conducting this research, the researchers determined the factors of behavior that affect the students from not making a recycled product. Therefore, the researchers now are giving tips about doing recycled products as a solution to the problem. The researchers used the qualitative method. The research involved 50 selected grade 12 ABM Strandstudents. Three variables, such as saving money from buying new raw materials and enhancing the creativity of the students regarding arts, were the advantages of recycling. Creativeness a behavior that is serves as an advantage from recycling. Recycling will avoid the high cost of purchasing new products. Instead of buying raw materials, the students can also practice their skills in innovating things, and they can also sell recycled products at an affordable price. The study showed that wrong behavior could lead to improper waste disposal, which can affect the environment. This result also showed how people should act accordingly. The students will also learn how to make recycled products that will benefit the environment and themselves.